Energy analysis of two-phase secondary refrigeration in steady-state operation, part 1: Global optimization and leading parameter. (15th October 2018) - Pons, Michel; Hoang, Hong-Minh; Dufour, Thomas; Fournaison, Laurence; Delahaye, Anthony
Abstract: A great deal of attention is paid to secondary refrigeration as a means of reducing excessively high emissions of refrigerants (most of which have a potent greenhouse effect) due to leaks in large cooling units. Among the environmentally friendly fluids that can be used in secondary circuits for transporting and storing cold, hydrate slurries offer the advantage of significant latent heats of fusion associated with good fluidity. Research programs have focused attention on hydrate systems, including CO2, TBPB (tetra- n -butyl-phosphonium-bromide), and mixed CO2 -TBPB hydrates. In addition to feasibility concerns, energy efficiency is also a crucial concern requiring an objective analysis of the improvements likely to result from these new materials. An impartial framework was thus constructed based on the principles of optimization methods. This approach was applied to these three hydrate slurries as well as to the well-known ice slurry for comparison purposes. A numerical model of secondary refrigeration system in steady state was built, on the basis of which optimized systems subjected to common external constraints can be designed for each slurry according to its thermophysical properties. Global performance can then be compared on a sound basis, which also makes it possible to identify the hydrate property that is most influential on energetic performance. Part 2 of this study is dedicated to exergy analysis and phase change kinetics. Highlights: Global optimization must be conducted with explicit constraints. Energy efficiency can be optimized only globally, i.e. including the primary cycle. The process design is optimized independently for each slurry. Each slurry presents an optimum for the maximal solid mass fraction in the process. Energy efficiency mainly depends on melting temperature.